Contemporary Asian Family: Its Crisis and Opportunity - Kochuthara, Shaji George (Asian Horizons, 2013)
Asia is traditionally known for the stability of the family system. In spite of the growing disintegration of the family in many parts of the world, to a great extent Asia can still boast of its stable families. Religious and cultural traditions in Asia have been giving great importance to family and its well being. However, drastic changes in the structure of the families, their life-style and values are visible in recent decades.